UNITARY EQUIVALENCE AND SIMILARITY OF ORDINARY SHIFTS ON OPERATOR VALUED WEIGHTED SEQUENCE SPACES - Orovčanec, Marija (Matematichki Bilten, 2001)
In this note we consider a number of properties of the operator valued weighted sequence spaces. We discuss similarity and unitary equivalence of unilateral unweighted shifts on operator valued weighted sequence spaces.